2015
DOI: 10.3139/217.3097
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Amides as Slip Additives in Polypropylene

Abstract: In this study, we describe the synthesis of amides and evaluate their use as slip additive agents in polypropylene films. The additives N-isopropyl-stearamide and N,N-diisopropyl-stearamide were synthesized and characterized and then used to prepare masterbatches. Erucamide, a commercial masterbatch, was used as the reference standard. A 32 factorial experimental design was used to create the different compositions of slip additives in polymer films. The films were processed via flat-die extrusion and stored i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Very little has been reported in the literature on slip additives diffusion, such as erucamide, oleamide, stearamide, and stearyl erucamide. The works of Cohen and Tabor, [ 16 ] Briscoe et al, [ 17 ] Ramírez et al, [ 18,19 ] Dulal et al, [ 20 ] Coelho et al, [ 21 ] and Quijada‐Garrido et al [ 12 ] have reported the CoF values for stearamide, behenamide, and erucamide in polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Very little has been reported in the literature on slip additives diffusion, such as erucamide, oleamide, stearamide, and stearyl erucamide. The works of Cohen and Tabor, [ 16 ] Briscoe et al, [ 17 ] Ramírez et al, [ 18,19 ] Dulal et al, [ 20 ] Coelho et al, [ 21 ] and Quijada‐Garrido et al [ 12 ] have reported the CoF values for stearamide, behenamide, and erucamide in polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…13-docosenamide was present in all the samples analyzed, while octadecanamide and hexadecanamide were only identified in three samples (AS_02, AS_04 and GA_02). They are able to reduce friction resistance and all of them belong to Class III according to Cramer rules [ 21 , 36 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even more, experimental results have shown that the COF depends on the hydrocarbon chain length of the FAs 4,10 , the extrusion time 11 , the surface concentration of FAs 8,9,12 , and the aging of the sample 5,9 . One of the most popular slip agents is erucamide; this fluid-friction reducing molecule is obtained from naturally occurring fats and oils frequently used in the polymer industry [6][7][8][9]13 .…”
mentioning
confidence: 99%
“…Additives have been used for years as sliding agents to modify the tribological properties of thin films [1][2][3] . Functionalized polymethylmethacrylate (PMMA) 4 and polyolefines (POs) 3,[5][6][7][8][9] surfaces with brushes composed by fatty acids (FAs) have proved to be useful to reduce the coefficient of friction (COF) of these materials. Even more, experimental results have shown that the COF depends on the hydrocarbon chain length of the FAs 4,10 , the extrusion time 11 , the surface concentration of FAs 8,9,12 , and the aging of the sample 5,9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation